FACTORS THAT LIMIT ACCESS TO DENTAL CARE FOR PERSON WITH DISABILITIES: Access To Dental Care for Disabled - Ishaque, M Yasir; Rahim, Shoaib; Hussain, M Hamaza (Pakistan Armed Forces Medical Journal, 2016)
Objective: To assess the perceived barriers to oral health care for persons with disabilities living in Islamabad.Study Design: Cross-sectional study.Place and Duration of Study: Study was conducted at general community organizations in Islamabad providing services to Persons with Disabilities (PWDs) from Jan 2013 to Jun 2013 over a period of 6 months.Material and Methods: A total of 500 persons with disability who were dependent on someone to reach dental facilities were included in the study while those who were not dependent on someone were excluded from the study. A 12-item self-administered questionnaire was used. Patient’s demographic data, type of disability and barriers to oral health care were recorded. Finally data was analyzed by using SPSS version 20.Results: Out of 400 respondents the most common disability was physical impairment (33.25%) followed by visual impairment (20.75%) and polio (14.75%). The major barriers to oral health care were transportation difficulty (48%) followed by high cost of dental treatment (39.5%) and inability to sit on dental chair /co-operate with dentist (31.25%).Conclusion: Significant barriers exist that limit the access to dental care for Person with Disabilities (PWDs).